2019
DOI: 10.3390/su11082387
|View full text |Cite
|
Sign up to set email alerts
|

Learning about Sustainable Mobility in Primary Schools from a Playful Perspective: A Focus Group Approach

Abstract: Nowadays, educational activities need to be oriented towards sustainable mobility as a tool to guarantee a better future for younger generations. Two focus groups (FGs) of children aged 10–12 years were formed, for the design, development, and evaluation of educational tools for gamification techniques on the subject of sustainable mobility. The study involved a group of children from three classes in the fifth-year of primary education at a school in the City of Burgos (Spain). The first focus group revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 29 publications
0
23
0
2
Order By: Relevance
“…Trends suggests a more theoretical approach at the beginning of the period studied, becoming more practical at the end, with a key influence from LARPs and Information and Communication Technologies (ICTs). For example, it can be observed that some topics are related to video games, two of them from a negative perspective [57,62], one about educational benefits [22], and finally a recent article about Classcraft [8], very related to MMORPGs [7,9]. Others are related to more physically interactive situations, like roleplaying [58,60,63] and LARPs [61] with applications for socialization, attitudes, and physical education, and several proposals including history [27,56], attitudes and values [30,55,60], mathematics [40], politics [59], sustainability [39], etc.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Trends suggests a more theoretical approach at the beginning of the period studied, becoming more practical at the end, with a key influence from LARPs and Information and Communication Technologies (ICTs). For example, it can be observed that some topics are related to video games, two of them from a negative perspective [57,62], one about educational benefits [22], and finally a recent article about Classcraft [8], very related to MMORPGs [7,9]. Others are related to more physically interactive situations, like roleplaying [58,60,63] and LARPs [61] with applications for socialization, attitudes, and physical education, and several proposals including history [27,56], attitudes and values [30,55,60], mathematics [40], politics [59], sustainability [39], etc.…”
Section: Resultsmentioning
confidence: 99%
“…Without the monograph from EKS in 2010, interest in the literature would not have been so strong. RPGs would have been found, especially compared with popularity of gamification [41,42,64], for example, with the use of Classcraft [7][8][9], or GBL. Both tendencies have a strong relationship with RPGs, a methodology with a huge potential in education [59].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, with the exponential growth of information and communication technology (ICT), mobile computing devices have become commonplace among university students [7,8]. Along with this trend, there also emerges a research interest in gamifying EE in recent years [9][10][11][12][13][14]. However, at present, it is not rare for university teachers to characterize mobile devices as detrimental to the quality of university education.…”
Section: Introductionmentioning
confidence: 99%